Respuestas

¡La mejor respuesta!
2013-09-06T00:45:04+02:00

4x-2=7x-(x+3)+(-x-6)
4x - 2 = 7x - x - 3 -x - 6
4x - 5x = - 9 + 2
          - x = - 7                      x =  7

8-(3x+3)=x-(2x+1)      .
8 - 3x - 3 = x - 2x -2
      - 3x + x = - 2 - 5
                - 2x = - 7            x = 7/2

2x+[2x-(x-4)]=-[x-(5-x)]
2x +(2x - x + 4) = - (x - 5 + x)
          2x + x + 4 = - 2x + 5
                   3x + 2x = 5 - 4
                           5x = 1                 x = 1/5

x-{5+3x-[5x-(6+x)]}=-3
x - {5 + 3x -(5x - 6 - x)} = - 3
x - {5 + 3x - 4x + 6)} = - 3
x - 11 + x  = - 3
         2x = - 3 + 11
         2x = 8                      x = 4

-{7x+[-4x+(-2+4x)]-(5x+1)}=0
- {7x + [- 4x - 2 + 4x] - 5x - 1} = 0
- {7x - 2 -  5x - 1} = 0
             - 2x + 3 = 0
              -2x = - 3             x = 3/2
  • Usuario de Brainly
2013-09-06T06:56:01+02:00
4x-2=7x-(x+3)+(-x-6)
4x - 2 = 7x - x - 3  -x - 6
4x - 2 = 7x -x -x - 3 - 6            juntamos las x y los numeros
4x - 7x + x +x = - 3 - 6 + 2
 -x = - 7
  x = 7

8-(3x+3)=x-(2x+1)
8 - 3x - 3 = x - 2x - 1
8 - 3 + 1 = x - 2x + 3x
6 = 2x
6/2 = x
3 = x

2x+[2x-(x-4)]=-[x-(5-x)]
2x+[2x- x+ 4] = -[x-  5 + x]
2x +  x + 4 = - x + 5 - x
3x + 4 = - 2x + 5
3x + 2x = 5 - 4
5x = 1
x = 1/5
 
x-{5+3x-[5x-(6+x)]}=-3
x-{5+3x-[5x- 6 - x]}=-3
x-{5+3x- 4x + 6}=-3
x - 5 - 3x +  4x -  6= -3
2x = - 3 + 5 + 6
2x = 8
x = 8/2
x = 4


-{7x+[-4x+(-2+4x)]-(5x+1)}=0

-{7x+[-4x -2 + 4x ]- 5x- 1} = 0
-{7x -4x -2 + 4x - 5x- 1} = 0
-  7x +4x +2 -  4x + 5x + 1 = 0
- 7x + 4x - 4x + 5x = -1 - 2
- 2x = - 3
x = - 3/-2
x = 3/2

espero que te sirva, salu2!!!!!